2015
DOI: 10.1007/s00128-015-1670-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Gibberellic Acid 3 (GA3) for Enhancing the Phytoremediation Efficiency of Solanum nigrum L.

Abstract: A microcosm experiment with artificially contaminated soils was conducted in a greenhouse to evaluate the effect of gibberellic acid 3 (GA3) on phytoremediation efficiency of Solanum nigrum L. The GA3 was applied at three different concentrations (10, 100, 1000 mg L(-1)) to S. nigrum. Results indicated that GA3 can significantly (p < 0.05) increase the biomass of S. nigrum by 56 % at 1000 mg L(-1). Concurrently, GA3 application increased Cd concentrations in the shoot of S. nigrum by 16 %. The combined effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Table 4 shows changes in pathways of energy metabolism induced by the arsenic presence that increase the glucose levels. Similar results have been obtained by other authors, which suggest impairments in energy metabolism and allow to suspect the occurrence of glycogenolysis, which indicates that energy reserves are mobilized for the metabolic needs of organisms under unfavorable conditions [44,45]. The increased levels of creatinine and creatine (Table 4) in digestive gland also suggest the alteration of energy metabolism after arsenic exposure.…”
Section: Metabonomic Study In Scrobicularia Plana Under Arsenic Exposuresupporting
confidence: 87%
“…Table 4 shows changes in pathways of energy metabolism induced by the arsenic presence that increase the glucose levels. Similar results have been obtained by other authors, which suggest impairments in energy metabolism and allow to suspect the occurrence of glycogenolysis, which indicates that energy reserves are mobilized for the metabolic needs of organisms under unfavorable conditions [44,45]. The increased levels of creatinine and creatine (Table 4) in digestive gland also suggest the alteration of energy metabolism after arsenic exposure.…”
Section: Metabonomic Study In Scrobicularia Plana Under Arsenic Exposuresupporting
confidence: 87%
“…Exogenous applications of GA 3 have a remarkable role in S. nigrum for substantial increases in growth and development [13]. In addition, a considerable increase in growth and biomass accumulation of Carapichea ipecauanha was observed in plants that received foliar applied GA 3 as compared to untreated plants [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellic acid (GA 3 ) is a plant hormone involved in several stages such as cell division, plant height, tissue differentiation, dry matter accumulation, net assimilation rate, leaf expansion, elongation, flowering, photosynthesis, and transpiration rate [9][10][11]. In addition, GA 3 is a kind of diterpenoid compound, and is known to play key roles to enhance phytoremediation efficiency of many crops by mediating physiology, morphology, and enzymatic activities [12,13]. Previous literature reported that exogenous supplementation of GA 3 as foliar spray significantly enhanced growth and phytoextraction efficiency of different crop plants such as Zea mays L., Tagetes patula L., Solanum nigrum L., and Corchorus capsularis L. grown on Cu, cadmium (Cd), lead (Pb), and benzo[a]pyrene-contaminated soil [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytoremediation technique for treating heavy metal contaminated soil includes phytoextraction, phytostabilization, rhizofiltration and phytovolatilization . Recent progress in phytoremediation aiming to curb heavy metal pollution has focused on the screening of suitable plant species that are potential heavy metal accumulators, such as Solanum nigrum , Helianthus annuus , Sorghum bicolor , Zea mays and Boehmeria nivea . Ramie ( Boehmeria nivea ) is conisidered to have excellent qualities for enduring heavy metal pollution and is considered as an ideal economic crop for the phytoremediation of mild or moderately heavy metal polluted areas as a result of several ramie varieties performing hyperaccumulative characteristics on heavy metals .…”
mentioning
confidence: 99%